Job Satisfaction and Performance: The Impact of Interpersonal Communication, Placement and Self Efficacy - Andary Nur Afifah,; Meylani Tuti, (Jurnal Manajemen, 2023)
Employee work happiness may be influenced by self-efficacy, interpersonal communication, and job placement, which in turn increases performance. The goal of this study was to examine how work placement, interpersonal communication, and elf effectiveness affected job performance and satisfaction. Employees of the National Police Headquarters SSDM made up the study's sample. Simple random sampling was used to collect samples from the 151 employees from several division who agreed to complete a questionnaire. A structural equation model (SEM) employing smart PLS software is used in the analytical procedure. The study's findings indicate that self-efficacy and interpersonal communication have a substantial impact on job satisfaction and performance. The significance of confidence and interpersonal communication in achieving employee job satisfaction to produce maximum performance.